Types of audit quality research: their advantages and disadvantages - Vaicekauskas, Darius (Buhalterinės apskaitos teorija ir praktika, 2013)
There is no single common definition of audit quality. Audit quality depends upon the observer, as well as on methods used in order to evaluate it. Considering that audit quality is usually an object under the investigation of three groups of stakeholders - external users, preparers and supervision authorities – three types of audit quality researches can be determined. In accordance to laws applicable in different countries, auditors and audit firms are usually periodically inspected by professional competent inspectors. The inspectors assess whether the firms and auditors do not infringe the provisions of auditing standards, national auditing laws, as well as how they manage internal resources and policies to provide high quality auditing services. These inspections could be performed only on legal basis by legally affirmed inspectors and their findings usually reach other stakeholders only if outrage deficiencies are detected. This lead to high quality assessments costs for other stakeholders to evaluate audit quality this way. In order to reduce quality assessment costs, external users apply audit quality surrogate researches – they employ various surrogates, which in their opinion, are closely tied with the audit quality (probability that auditors will detect deficiencies and will react properly) and assess whether these surrogates are applicable to particular audit firm. Surrogates such as audit firm size, auditor’s tenure, non-audit services provided to audit clients are often employed. Although these researches may be informative and interesting to various analytics and scientists, the lack of particular necessary information and difficult mathematical-statistical models reduce the quantity of such researches. Due to audit clients’ direct interaction with their auditors, clients do not rely on surrogates – they evaluate audit quality on their own perceptions. Usually these perceptions are based on various attributes of an audit firm (size, brand, reputation) and audit team (empathy, communication, responsiveness). That kind of research does not focus on defining audit quality, it is more leaning towards the attributes, existence of which in engagements causes clients’ perceptions of audit as of good quality. Literature analysis shows that due to increasing interest in an audit quality subject, various different types of audit quality researches will arise in the future.